THE IMPORTANCE OF CHEMISTRY IN CRIMINOLOGY. (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation. In this article, information about criminology and a significance of chemistry in criminalistics and examples of it described in detail.